A Study on Factors Affecting the E-Money Adoption in Aceh - Rasyidin, M; Hartati, Sri; Nova, N; Zulfikar, Z; Saleh, M; Rizal, Muhammad (SAINTIS Publishing, 2024)
This study aims to investigate the impact of understanding and perceived usefulness on the interest in using e-money in Aceh Province. The research employs a quantitative approach, targeting e-money users in the region. A purposive sampling technique was utilized, resulting in a sample size of 133 participants, selected via the Unknown Populations method. Data were collected via questionnaires distributed through Google Forms. The analysis involved validity, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, and regression analysis tests (ANOVA). The model applied was multiple linear regression analysis. Findings indicate that understanding has a positive and significant effect on the interest in using e-money, while perceived usefulness also positively and significantly influences this interest.